2015
DOI: 10.1590/0102-311x00014515
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sugar-rich food products among Brazilian students:National School Health Survey (PeNSE 2012)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(61 reference statements)
0
5
0
1
Order By: Relevance
“…23 Although the factors previously mentioned may reflect sedentary leisure habits, our study showed that the practice of physical activity was not associated with the consumption of UPF independently. As pointed out in other studies with Brazilian adolescents, 4,21 this means that sedentary habits are more determinant for the consumption of UPF among adolescents in PeNSE-2015 than not practicing physical activity as recommended (300 minutes). 11 The habit of eating while watching TV or studying was also associated with excessive consumption of UPF.…”
Section: Discussionmentioning
confidence: 64%
“…23 Although the factors previously mentioned may reflect sedentary leisure habits, our study showed that the practice of physical activity was not associated with the consumption of UPF independently. As pointed out in other studies with Brazilian adolescents, 4,21 this means that sedentary habits are more determinant for the consumption of UPF among adolescents in PeNSE-2015 than not practicing physical activity as recommended (300 minutes). 11 The habit of eating while watching TV or studying was also associated with excessive consumption of UPF.…”
Section: Discussionmentioning
confidence: 64%
“…A significant intake of cookies and sugar-sweetened beverages was observed among adolescents in Brazil. The National School Health Survey (PeNSE 2012) found that 20% of 108,726 adolescents aged 14-16 years investigated regularly consume sweets and sodas [39].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of processed foods, including soft drinks (such as soda), and treats (candies, chewing gums, chocolates etc. ), is considerable among students in Brazil [12][13][14], especially among adolescents [15]. These foods are considered as "ultraprocessed" by the Food Guide for the Brazilian Population, whose nutritional composition is unbalanced, favoring the excessive consumption of calories and the substitution of in natura or minimally processed foods.…”
Section: Discussionmentioning
confidence: 99%